SOSIALISASI PROTOKOL KESEHATAN DAN VAKSINASI SERTA PELATIHAN MANAJEMEN KEUANGAN BAGI RUMAH TANGGA - Pratiwi, Fahrunisa; Risa, Nurma; Putra, Purnama (DEVOSI, 2022)
Since its appearance in 2019, the Covid-19 virus has quickly spread to various countries in the world. Indonesia is one of the countries with a fairly high number of positive COVID-19 cases. The high number of positive COVID-19 cases has prompted the Indonesian government to implement various policies to prevent the spread and transmission of Covid-19, starting with the imposition of Large-Scale Social Restrictions, the 5M Health Protocol Policy to the Covid-19 Vaccination Program. The purpose of this Real Work Lecture activity is to help prevent the spread and transmission of Covid-19 in the Griya Alam Sentosa Housing Block P19 RT 01 neighborhood through online socialization. Based on the results of the pre-test and post-test, there was an increase in the understanding and behavior of community prevention before and after the socialization. Other problems that have arisen due to the Covid-19 pandemic are the weakening of the economy, some people have difficulty in financial management because people have not planned well. The household financial management socialization and training program with the Money Lover application is carried out with the aim of helping the community in carrying out good financial management so that expenses are not greater than their income so as to avoid being dependent on debt with someone or a money lending institution.